PENGOBATAN TRADISIONAL SEBUAH KAJIAN INTERAKSIONISME SIMBOLIK - Hendri Setiawan; Faizal Kurniawan (IKIP Budi Utomo Malang, 2017)
People have a belief in finding different healing from one another. Some people entrusted to medical treatments, and the others entrusted to traditional treatments. Those who did traditional treatments believe that because of their culture which forms the society’s behavior to entrust healing through traditional treatment. For the people of Desa Tutut Arjowinangun Malang, Pengobatan tradisional is a socio-cultural treatment or treatment based on culture. Pengobatan Tradisional here uses a dream interpretation that can only be done by the healer or shaman Pengobatan Tradisional. The solution of the pain suffered by the patient is derived from a dukun’s dream interpretation and combined with the ritual of giving salt to the patient. The ability of healers, shamans, or healers to carry out traditional medical practices is not obtained by chance or by accident, but by a certain stage or ritual. A healer or dukun has the ability to carry out his traditional treatment practices also through the possession of heirlooms. They are like kris and or ancient weapons in the past, stone, jewelry, and so on. These heritage objects are believed to give a power to perform a ritual both for treatment and other activities that can not be done by most humans. In addition to some of the explanations that have been outlined above, traditional medicine still has a place in the Society due to the support of the surrounding community. The village community of Tutut Arjowinangun gives trust to the dukun Pengobatan Tradisional to provide an alternative for healing. The community of Desa Tutut Arjowinangun Malang has different perception about illness. The majority of Tutut Arjowinangun Malang Village people interprete medical illness as a disturbance of the body’s metabolic system. But the people of Desa Tutut Arjowinangun Malang who still adhere to cultural values will certainly have different perception on the pain. As Foster points out that a personalistic system is a system in which illness is caused by the intervention of an active agent, an active agent here being a supernatural being. These supernatural beings are like supernatural beings or gods, non-human beings such as ghosts, ancestral spirits or evil spirits as well as human beings in the form of sorcerers or sorcerers. So here the sick person is the victim, the object of aggression or punishment specifically directed to him for special reasons concerning him alone.